1995
DOI: 10.1269/jrr.36.112
|View full text |Cite
|
Sign up to set email alerts
|

Immediate-early, Transient Induction of the Interleukin-1.BETA. Gene in Mouse Spleen Macrophages by Ionizing Radiation.

Abstract: In murine spleen cells, x ray irradiation induces the expression of the IL-1 beta gene at multiple phases of the peak time. We analyzed the immediate-early phase of IL-1 beta mRNA accumulation. To determine the lineage of cells that showed the immediate response to irradiation, normal spleen cells were analyzed by Northern blotting and in situ hybridization after separation by magnetic antibodies against specific cell-surface antigens. Although most of the spleen macrophages continuously expressed a low level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Multiple studies have reported that ionizing radiation leads to increased expression of proinflammatory cytokines [92][93][94] as well as inducing inflammasome pathway activation in immune cell populations [95]. Our analysis revealed several changes consistent with a heightened inflammatory milieu.…”
Section: Discussionsupporting
confidence: 57%
“…Multiple studies have reported that ionizing radiation leads to increased expression of proinflammatory cytokines [92][93][94] as well as inducing inflammasome pathway activation in immune cell populations [95]. Our analysis revealed several changes consistent with a heightened inflammatory milieu.…”
Section: Discussionsupporting
confidence: 57%
“…Increased expression of proinflammatory cytokines, including TNF-a and IL-1b following radiation has been reported by some authors (Hallahan et al,1989;Ishihara et al, 1995;Nemoto et al, 1995). These observations suggest a potential role for radiation in signaling 'danger' and, perhaps, in the activation of antigen presenting cells (McBride et al, 2004).…”
Section: The Role Of Radiation 211 Immunomodulatory Effects Of Radimentioning
confidence: 53%
“…The mechanism of this delayed effect is not clear. It has been recently shown that activation of the IL-1~pathway due to direct effects of irradiation can occur at transcriptional, translational, and post-translational levels and involves a stress-sensitive CASP-I signaling platform (31,(33)(34). The activation of these events requires minutes to hours (31,(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that activation of the IL-1~pathway due to direct effects of irradiation can occur at transcriptional, translational, and post-translational levels and involves a stress-sensitive CASP-I signaling platform (31,(33)(34). The activation of these events requires minutes to hours (31,(33)(34). We did not find a significant difference of the ileal IL-I~levels between sham and irradiated mice at the 2 nd day of observations despite increased IL-I~levels in blood plasma (not shown).…”
Section: Discussionmentioning
confidence: 99%